2020
DOI: 10.3390/ijms21124559
|View full text |Cite
|
Sign up to set email alerts
|

Familial Infertility (Azoospermia and Cryptozoospermia) in Two Brothers—Carriers of t(1;7) Complex Chromosomal Rearrangement (CCR):  Molecular Cytogenetic Analysis

Abstract: Structural aberrations involving more than two breakpoints on two or more chromosomes are known as complex chromosomal rearrangements (CCRs). They can reduce fertility through gametogenesis arrest developed due to disrupted chromosomal pairing in the pachytene stage. We present a familial case of two infertile brothers (with azoospermia and cryptozoospermia) and their mother, carriers of an exceptional type of CCR involving chromosomes 1 and 7 and three breakpoints. The aim was to identify whether meiotic disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…According to the classification of CCRs, this case is considered a double CCR. Within more than 250 cases related to CCRs published thus far, 161 cases concerned male CCR carriers (Olszewska et al, 2020). Approximately 75% of CCRs appear de novo or are inherited maternally (70% of all familial cases) (Pellestor et al, 2011;Olszewska et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the classification of CCRs, this case is considered a double CCR. Within more than 250 cases related to CCRs published thus far, 161 cases concerned male CCR carriers (Olszewska et al, 2020). Approximately 75% of CCRs appear de novo or are inherited maternally (70% of all familial cases) (Pellestor et al, 2011;Olszewska et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Within more than 250 cases related to CCRs published thus far, 161 cases concerned male CCR carriers ( Olszewska et al, 2020 ). Approximately 75% of CCRs appear de novo or are inherited maternally (70% of all familial cases) ( Pellestor et al, 2011 ; Olszewska et al, 2020 ). To date, most men with CCRs have serious fertility problems due to spermatogenesis disorders ( Salahshourifar et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…9,25 Indeed, the meiosis I prophase checkpoint is supposed to be less permissive in men than in women, and spermatogenesis is consequently strongly disturbed by complex changes. 11,26,27 During the first division of meiosis, homologous chromosome pairing is a critical step and will be followed by crossing-over. In case of CCR, this step is disturbed and can be completed only through the formation of complex loops between homologs in order to avoid asynaptic segments.…”
Section: Discussionmentioning
confidence: 99%
“…1,9 It has also been observed that chiasmata numbers are reduced in complex rearrangements, leading to less frequent recombination events. 10,11 Nevertheless, stable and unstable transmissions of chromoanagenesis have been reported. [12][13][14][15][16][17][18][19] We report here six families with one parent presenting chromoanagenesis with unstable transmission of the CCR to the offspring, resulting in congenital disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation